Access to dental services and oral health-related quality of life in the context of primary health care - Lucelen Fontoura BASTOS; Fernando Neves HUGO; Juliana Balbinot HILGERT; Débora Deus CARDOZO; Alexandre Fávero BULGARELLI; Camila Mello dos SANTOS
Abstract The aim of the present study was to evaluate the association between access to oral health care in the Primary Health Care (PHC) and Oral Health-Related Quality of Life (OHRQoL). The present study was a cross-sectional study, and the sample was composed of 412 users living in the areas covered by the public PHC services who visited a health unit for an oral exam or treatment in the last 24 months. Participants in the study responded to a home-based interview with questions that addressed socioeconomic status, behavioral, general health, dental prostheses, access to dental services in the PHC and their OHRQoL as measured by the Oral Health Impact Profile (OHIP-14) instrument. After the interview, a dental examination was performed to count the number of teeth. Chi-square tests, Student's t tests and multivariate analyses were performed using a hierarchical model and a Poisson regression with robust variance to evaluate the association between independent variables and OHRQoL. Access to oral health services in the PHC was statistically associated with OHRQoL, and the estimated prevalence rate was PR = 1.17 (CI 95% 1.00-1.37). In this study, the definition of access was based on the availability of dental consultations on demand. The study identified that lack of access to oral health services offered by the PHC was associated with a higher prevalence of impact on the quality of life of individuals.